Psychological reactance to anti-smoking campaigns in designated smoking areas among female smokers in their 20s and 30s: a quasi-experimental study - Hyeonji Mun; Soontae An; Hyekyeong Kim (Journal of Korean Academy of Nursing, 2026)
Purpose: This study aimed to determine whether placing anti-smoking campaign messages in designated smoking areas elicits psychological reactance among female smokers and to assess whether message framing (controlling vs. non-controlling) moderates the association between psychological reactance and intention to quit smoking.Methods: A quasi-experimental survey was conducted with 259 female smokers. Of these, 58 participants completed the survey before exposure to smoking-cessation messages, and 201 completed the survey after exposure. Among the exposed participants, 100 were assigned to the controlling condition and 101 to the non-controlling condition. Measures included psychological reactance, intention to quit smoking, trait reactance, smoking disclosure, and smoking-related covariates. Data were analyzed using analysis of covariance and Hayes’ PROCESS Model 1, with statistical significance set at p